2018
DOI: 10.1080/24750158.2018.1534281
|View full text |Cite
|
Sign up to set email alerts
|

Library Anxiety: Stories, Theories and Possible Solutions

Abstract: This issue, in collaboration with the State Library of New South Wales, we are pleased to feature the 2018 winner of the Jean Arnot Memorial Fellowship. The Fellowship is awarded to a female librarian or student of librarianship for an outstanding paper of no more than 5000 words on any aspect of librarianship. Papers focusing on innovative solutions to contemporary library issues and services are encouraged. The fellowship is named in honour of the late Jean Fleming Arnot, MBE, FLAA, a former staff member of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…Radford and Radford argue that representations of libraries and librarians in film and popular culture participate in a “discourse of fear”. That is, the way libraries are depicted in popular culture reinforces negative stereotypes regarding the physical library that further alienate library users (Shelmerdine, 2018; Nieves-Whitmore, 2021). Tancheva argues that the image of “the library”, and by extension “the librarian”, is not only part of public discourse of fear but is also part of the discourse of the library as a profession.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Radford and Radford argue that representations of libraries and librarians in film and popular culture participate in a “discourse of fear”. That is, the way libraries are depicted in popular culture reinforces negative stereotypes regarding the physical library that further alienate library users (Shelmerdine, 2018; Nieves-Whitmore, 2021). Tancheva argues that the image of “the library”, and by extension “the librarian”, is not only part of public discourse of fear but is also part of the discourse of the library as a profession.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Library anxiety was examined by McPherson (2015), who found both personal and institutional factors as causes among undergraduate students. Shelmerdine (2018) explored the work of Carl Rogers on invitational theory as a lens through which to consider library anxiety and concluded that librarianship has close parallels with the helping professions. A study by Fraser and Bartlett (2018) examined racial differences in library anxiety in a Canadian context.…”
Section: Building Institutional Literacymentioning
confidence: 99%
“…They asserted that a personal librarian program can reorient students by providing bearings and modeling behaviour in the physical and virtual spaces of the library, because the librarians have a relationship with the students. The importance of relationships with librarians in addressing library anxiety was also highlighted by Shelmerdine (2018). This might simply be a relationship of sending and reading emails, but even that can be the starting point for a new student trying to find their way.…”
Section: Program Implementationmentioning
confidence: 99%
“…Undergraduates, always the newest users of the library, often exhibit the symptoms of library anxiety (McPherson, 2015;Shelmerdine, 2018); hence, a chatbot focused on their early entry into university offers an opportunity to condition how new students perceive research and library services. A closer look at the features of chatbots will highlight how they can be used to achieve this goal.…”
Section: Role Of the Lib-botmentioning
confidence: 99%
“…This is done through reflection on the ongoing process of chatbot development at the University of Technology, Sydney (UTS) Library, incorporated with reflection on relevant literature and thus takes a narrative rather than empirical approach. We argue that chatbots can provide new library users, generally undergraduate students, with a sense of ease in using the library resources, while minimising the effects of library anxiety related to research, library databases and librarian services (McPherson, 2015;Shelmerdine, 2018). Most users are already familiar with chatbots in other contexts in their everyday life, using them for example to find items on their phone with Apple's Siri, search their computer with Window's Cortana, or navigate the internet with Ok Google or Amazon's Alexa.…”
Section: Introductionmentioning
confidence: 99%